LEGAL PROTECTION FOR MIDWIVES PERFORMING MEDICAL PROCEDURES (CASE STUDY OF BANDUNG KEBONJATI HOSPITAL) - Susiswo Susiswo; S. E Rayung Wulan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
Legal protection can be the right of every individual, incl midwife. Moment this, Still A little which discuss about Midwife legal protection at Kebonjati Hospital Bandung. This study aims to discuss more deeply the legal protection for midwives who carry out medical procedures at Kebonjati Hospital in Bandung. Which method used to achieve this goal, namely legal research normative, using primary and legal material sources secondary. Results study show midwife own authority in carry out his job in House Sick. This authority is evaluated by professional organizations so that it does not take action beyond the authority that results on consequence law. Protection law to midwife conducted by the Indonesian Midwives Association (IBI). If happen violation which resulted midwives under to the realm court, then a review is carried out by IBI through MPA IBI and MPEB IBI. If the midwife concerned runs the standard profession, service standards and standard operating procedures, then Legal assistance will be provided by IBI in facing demands or lawsuits in court.